2017
DOI: 10.1016/j.tourman.2017.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Exploring corporate social responsibility and financial performance through stakeholder theory in the tourism industries

Abstract: The literature examining the relationship between corporate social responsibility (CSR) and corporate financial performance (CFP) in the tourism industries is extensive but it has not verified the relationship unambiguously. This has been attributed to the methodological artefacts used, but also to the lack of a solid theoretical foundation. Based on stakeholder theory, this paper proposes the use of two models that explicitly investigate the relationship between stakeholder management, expressed as CSR activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
164
1
15

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(186 citation statements)
references
References 54 publications
6
164
1
15
Order By: Relevance
“…Lastly, it is normative because stakeholders are accepted as groups having an interest in the organization and vice versa, while they are intrinsically motivated [27]. Regarding research in the tourism field, some results support an instrumental perspective, while the normative perspective is neglected [29].…”
Section: Stakeholder Theory and Its Application To Sustainable Tourismentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, it is normative because stakeholders are accepted as groups having an interest in the organization and vice versa, while they are intrinsically motivated [27]. Regarding research in the tourism field, some results support an instrumental perspective, while the normative perspective is neglected [29].…”
Section: Stakeholder Theory and Its Application To Sustainable Tourismentioning
confidence: 99%
“…In this setting, DMOs are responsible for coordinating firms' communication and strategic orientation [18]. In addition, tourism research emphasizes social and environmental effects [29]. The interaction effects of strategy and corporate social responsibility (CSR) variables, such as selling intensity, community activities, and improving financial performance, while moderating strategy variables and diversity activities, positively influence environmental performance [29].…”
Section: Family Firms As Major Tourism Stakeholdersmentioning
confidence: 99%
“…Corporate social responsibility (CSR) describes firms' discretionary business initiatives that improve societal well-being beyond that which is commanded by law [17,18]. Recently, studies exploring CSR initiatives in the tourism context have emerged and been applied to various tourism-related industries, such as the airline industry [19], the cruise industry [20], the restaurant context [21][22][23], the casino industry [24,25], the hotel industry [26,27], and the tourism-related contexts (i.e., airlines, hotels, restaurants, and casinos) [28,29]. However, the assessment of CSR in the destination context (destination social responsibility) may vary from the previous traditional CSR research.…”
Section: Destination Social Responsibility and Pro-tourism Behaviorsmentioning
confidence: 99%
“…On the basis of the stakeholder theory, firms leverage CSR activities to exert an impact on various stakeholders, including tourists, employees, and community residents [30]. The extant tourism CSR research has started to consider CSR actions primarily as connections to shareholders' values [22,29], customers' behavior [31,32], employee-associated outcomes [25,26], and residents' attitudes and support [11,16]. Therefore, the following hypothesized relationship is proposed: Hypothesis 1 (H1).…”
Section: Destination Social Responsibility and Pro-tourism Behaviorsmentioning
confidence: 99%
“…For instance, Harjoto and Jo [7] found that legalized sustainability exposure due to governmental requirements is in favour of the market because the information is more likely to be genuine and less costly to access. Theodoulidis et al [8] indicated that sustainability engagement information increases market confidence as long-run-oriented business strategy eliminates stock market speculators. However, when a company discloses information about sustainability engagement, there are two general arguments among the existing studies about how the market interprets the information.…”
Section: Introductionmentioning
confidence: 99%